Biomarkers in Breast Cancer: An Integrated Analysis of Comprehensive Genomic Profiling and PD‐L1 Immunohistochemistry Biomarkers in 312 Patients with Breast Cancer. (14th September 2020) - Huang, Richard S.P.; Li, Xinyan; Haberberger, James; Sokol, Ethan; Severson, Eric; Duncan, Daniel L.; Hemmerich, Amanda; Edgerly, Claire; Williams, Erik; Elvin, Julia; Vergilio, Jo‐Anne; Killian, Jonathan Keith; et al.
Abstract: Background: We examined the current biomarker landscape in breast cancer when programmed death‐ligand 1 (PD‐L1) testing is integrated with comprehensive genomic profiling (CGP). Material and Methods: We analyzed data from samples of 312 consecutive patients with breast carcinoma tested with both CGP and PD‐L1 (SP142) immunohistochemistry (IHC) during routine clinical care. These samples were stratified into hormone receptor positive (HR+)/human epidermal growth factor receptor negative (HER2−; n = 159), HER2‐positive ( n = 32), and triple‐negative breast cancer (TNBC) cohorts ( n = 121). Results: We found that in the TNBC cohort, 43% (52/121) were immunocyte PD‐L1–positive, and in the HR+/HER2− cohort, 30% (48/159) had PIK3CA companion diagnostics mutations, and hence were potentially eligible for atezolizumab plus nab‐paclitaxel or alpelisib plus fulvestrant, respectively. Of the remaining 212 patients, 10.4% (22/212) had a BRCA1/2 mutation, which, if confirmed by germline testing, would allow olaparib plus talazoparib therapy. Of the remaining 190 patients, 169 (88.9%) were positive for another therapy‐associated marker or a marker that would potentially qualify the patient for a clinical trial. In addition, we examined the relationship between immunocyte PD‐L1 positivity and different tumor mutation burden (TMB) cutoffs and found that when a TMB cutoff of ≥9 mutations per Mb was applied (cutoff determined based on prior publication), 11.6% (14/121) patients were TMB ≥9 mutations/Mb and of these, TMB ≥9 mutations per Mb, 71.4% (10/14) were also positive for PD‐L1 IHC. Conclusion: Our integrated PD‐L1 and CGP methodology identified 32% of the tested patients as potentially eligible for at least one of the two new Food and Drug Administration approved therapies, atezolizumab or alpelisib, and an additional 61.2% (191/312) had other biomarker‐guided potential therapeutic options. Implications for Practice: This integrated programmed death‐ligand 1 immunohistochemistry and comprehensive genomic profiling methodology identified 32% of the tested patients as eligible for at least one of the two new Food and Drug Administration‐approved therapies, atezolizumab or alpelisib, and an additional 61.2% (191/312) had other biomarker‐guided potential therapeutic options. These findings suggest new research opportunities to evaluate the predictive utility of other commonly seen PIK3CA mutations in hormone receptor‐positive breast cancers and to standardize tumor mutation burden cutoffs to evaluate its potentially predictive role in triple‐negative breast cancer. Abstract : This article reports the current landscape of biomarkers in breast cancer, focusing on patients using comprehensive genomic profiling and PD‐L1 immunohistochemistry in addition to the previous standard of care diagnostics for hormone receptor and human epidermal receptor 2 identification. The relationship between different immunotherapy biomarkers in patients with triple‐negative breast cancer is examined.